PkM PADA ANAK USIA SEKOLAH DASAR: MENGEMBANGKAN BUDAYA LITERASI DI LINGKUNGAN TAWANG BRAK DESA TAWANGSARI, KEC. GARUM KAB. BLITAR - Fahmi Poernamawatie; Yuli Winarni (Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this community service activity is to help children of primary school age get used to writing and reading. This habit is expected to increase children's reading interest and develop their reading literacy culture.The implementation of this activity is done through various way of exercises, such as: reading exercises, rewriting and retelling. Children are also accustomed to read Al-Qur’an and praying together. Drawing and coloring are also steps taken by the community service team to hone children's creativity. Watching films and entrepreneurship exercises to complement this activity, so that children have broad insights and also practice to improve financial literacy.Even though this activity still not showing the significant impact to the reading and writing skills of the children, but this activity gives benefits in terms of increasing the interest in reading, writing, and retelling something new. Enterpreneurial skills of some participants have have also created at the end of the activity. To achieve more optimal results, this activities should be done regularly with well-planned schedule.